ANALISIS KEBIJAKAN DAN PROGRAM KEGIATAN DI PTAI RESPONSIF GENDER - Nurhamdah Nurhamdah (LPPM IAIN Parepare, 2016)
Since gender mainsteaming has not been institutionalized in particular on policies, and program related to gender planning and budgeting become one factor of the gender gap issues. The aim of this article is to find out the gender gap issues budgeting on Islamic Institution. Therefore, it needs to be done on gender analysis of policy which its results are used as a reference to reformulate policy that describe equality and provide benefits for academic community both men and women at STAIN Parepare. The result showed that there were no gender gap issues in the program of “Pengembangan Kegiatan Jurusan Tarbiyah”. This program has given students acsess to and participation in both men and women as users of development to be actively participate in the program. This also give control equally for both students to take apart in Tarbiyah program, thus the expected benefits attached to them as qualified students as mandated by the outcome of DIPA and RKAL STAIN Parepare.